Analisis Penerjemahan Kalimat Tanya dalam Subtitle Film "The Terminal" - Ghossan Fa'iq Harsanto; Sumardiono Sumardiono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study is qualitative descriptive research. The purpose of this research is to know kind of interrogative sentences and translation techniques impact to the translation quality in The Terminal movie subtitle. The source of data is the film transcript of The Terminal movie and its subtitle in Indonesian, and the information collected from rater. The technique of data collection was watching the movie, reading the script, and marking the interrogative sentences. In analyzing data, the researcher used the qualitative data analysis which covers domain analysis, taxonomic analysis, and componential analysis. Had been found 114 data, yes-no question (57,97%), wh-question (41,19%), and alternative question (0,87%), 2) the translation technique could be found in The Terminal movie, such as established equivalent (72,08%), variation (15,83%), pure borrowing (3,12%), modulation (2,91%), implicit (1,87%), paraphrase (1,25%), explicit (1,04%), reduction (0,83%), transposition (0,62%), generalization (0,20%), and substitution (0,20%). The impact of the application of those translation techniques, toward the translation quality is the overall quality score 2,98 with the average score of accuracy 2,97, acceptability 2,99, and readability 2,99. Keywords: Translation, Interrogative Sentences, Qualitative Descriptive, The Terminal